Edukasi Perilaku Hidup Bersih Dan Sehat (PHBS) Melalui Film Kartun Bagi Anak Paud - Prabowo, Aditya Eka; Dewa, Pasha; Imawan, Hamzah; Azzahra, Amellia Intania; Permadi, Aditya; Sandy, Regina; Hartono, Dwi; Yunasfi, Lutfiah Rahma; Azzahra, Vaniska Nesya; Darmawati, Idiani (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Education on Clean and Healthy Living Behavior (PHBS) education is an important aspect of disease prevention, especially in early childhood. Getting used to clean living from an early age not only protects children from the risk of infection, but also forms the basis of sustainable health. PHBS education for PAUD children is a preventive step to increase awareness of hygiene and health from an early age. The “Clean and Healthy Living Behavior Education (PHBS) through Cartoon Films for PAUD Children” program initiated by this service team aims to introduce PHBS interactively. Learning methods include showing educational cartoon films, interactive discussions, direct demonstrations, and simple material delivery. The results of the program indicate an increase in understanding and a positive change in children's attitudes toward hygiene practices, particularly in handwashing and consuming nutritious food. Previously, only 2 out of 14 children understood the correct handwashing steps, but after the program, this number increased to 10 out of 14, demonstrating the effectiveness of animated educational films as a teaching tool. These findings suggest that animated films are an effective method for instilling PHBS in early childhood and have the potential for broader application as a preventive effort to improve public health quality.